THE IMPACT OF THE MUZARA'AH PRODUCT SHARING SYSTEM IN THE CULTIVATION OF COFFEE LANDS IN KERINCI REGENCY, INDONESIA (Al Dzahab, 2024)
Purpose: The people of Kerinci Regency often do muzara'ah profit sharing called pduo in coffee land management. Therefore, the background of muzara'ah needs to be analyzed to determine the agreement system, the distribution of results, and the impact on the income of tenant farmers and landowners.Design/ Methodology/Approach: To get answers to the research objectives, qualitative research was conducted using a case study approach to obtain research results.Finding: The maharajah profit-sharing system is motivated by farmers who do not own land and have limited capital, landowners due to age, and other jobs such as traders and civil servants, so they do not have time to manage the land. Oral and non-verbal contracts with no witnesses present precede the management system. Muzara'ah profit sharing has a positive impact on increasing the income of tenant farmers and landowners.Research Implications: Based on this research's results, coffee farmers' income can be increased through the Muzara'ah profit-sharing system.Keywords: Muzara'ah; Coffee; Pduo; Management